Determination of the required segregation of fractions of sinter charge for stabilizing the thermal conditions of sintering - Мных, Антон Сергеевич; Ерёмин, Александр Олегович; Мных, Ирина Николаевна (Eastern-European Journal of Enterprise Technologies, 2015)
A methodology that allows a continuous real-time estimation of the fractional composition of the charge by the horizons of the layer, prepared for sintering is proposed in the paper. The concept of the coefficient, characterizing the change in the average diameter of the groups of fractions by the layer height was introduced, its values for the sintering machines of individual metallurgical plants were calculated. The adequacy of the developed method for sintering plants of different enterprises was verified. It was found that the method can be considered suitable for identifying the fractional composition of granular material, loaded on pallets. The required distribution of fractions of a polydisperse sinter charge that stabilizes the thermal conditions of the sintering process. The latter is caused by the optimal distribution of the solid fuel and the chemical components of the charge and creates prerequisites for selecting the feeder, capable of providing the desired fractions material segregation.